2020
DOI: 10.3389/fmicb.2020.01511
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Primary Infection and Reactivation: Insights From Virion-Carried Molecules

Abstract: Human cytomegalovirus (HCMV), a ubiquitous beta-herpesvirus, is able to establish lifelong latency after initial infection. Periodical reactivation occurs after immunosuppression, remaining a major cause of death in immunocompromised patients. HCMV has to reach a structural and functional balance with the host at its earliest entry. Virion-carried mediators are considered to play pivotal roles in viral adaptation into a new cellular environment upon entry. Additionally, one clear difference between primary inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 288 publications
0
25
0
Order By: Relevance
“…HCMV ori Lyt is the site of initiation of viral DNA synthesis. Previous studies have identified two essential regions within ori Lyt and core HCMV replication machinery ( 69 71 ). In addition to this core machinery, IE2 and the UL84 protein are required for viral genome replication ( 72 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…HCMV ori Lyt is the site of initiation of viral DNA synthesis. Previous studies have identified two essential regions within ori Lyt and core HCMV replication machinery ( 69 71 ). In addition to this core machinery, IE2 and the UL84 protein are required for viral genome replication ( 72 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…HCMV is an enveloped dsDNA betaherpesvirus within the family of Herpesviridae and is a common complication in immunocompromised patients. 90 HCMV infection leads to significant alterations of metabolism. HCMV can induce glycolysis and mitochondrial respiration.…”
Section: Human Cytomegalovirus (Hcmv)mentioning
confidence: 99%
“…Primary infection of healthy individuals with HCMV is typically asymptomatic, although it can present with mild flu-like symptoms. The virus replicates in a broad range of cell types; briefly, after entry via fusion or receptor-mediated endocytosis, the viral genome is delivered to the nucleus where it expresses a cascade of temporally regulated genes [ 2 ]. This is followed by capsid assembly, the acquisition of tegument proteins, envelopment in a lipid bilayer and egress of the new virions (reviewed in [ 2 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The virus replicates in a broad range of cell types; briefly, after entry via fusion or receptor-mediated endocytosis, the viral genome is delivered to the nucleus where it expresses a cascade of temporally regulated genes [ 2 ]. This is followed by capsid assembly, the acquisition of tegument proteins, envelopment in a lipid bilayer and egress of the new virions (reviewed in [ 2 ]). A rapid and robust antiviral response is mounted against HCMV, in which innate, cellular and humoral immunity play an important role [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%